BROKEN SU(8) AND HADRONIC MASS RELATIONS IN HEAVY-QUARK EFFECTIVE THEORY - Decamargo, A. F.; Ferreira, P. L.; Palladino, B. E. (World Scientific Publ Co Pte Ltd, 1995)
Mass relations for hadrons containing a single heavy quark (charm or beauty) are studied from the viewpoint of a quark model with broken SU(8) symmetry, developed by Hendry and Lichtenberg some time ago, in comparison to that of the heavy quark effective theory. The interplay of the two approaches is explored and spectroscopic consequences derived.